Os desafios e limites do trabalho profissional no Centro de Referência de Assistência Social (CRAS) São Sebastião Abaetetuba/PA, no contexto atual de regressão de direitos - FURTADO, Kelliane de Jesus Silva (2023)
The present work is a discussion of the challenges and limits of the professional work of social workers of the CRAS São Sebastião, located in the municipality of Abaetetuba/Pará. The CRAS is inserted in a reality of the amazon, demarcated by own peculiarities, however, participant of reality that introduces the national level. From a current situation in approach that escalate the expressions of social issues, marked by measures of budget cuts, against reforms and proposals for constitutional amendments that benefiting the interests of capitalism to the detriment of socially rights conquered, aimed to analyze the performance of the professional social workers in this space, seeking to understand the implementation of the Social Assistance Policy, identifying the limits and challenges posed to professionals, and endorsed the importance of the ethical-political professional project of social workers for emancipating practices . To reach the objectives, bibliographic, documentary and field research was used. The bibliographical research explored authors discussing about social policy: social assistance, about the profession of social work and its ethical-political Project. The authors used in the bibliographic research, from a critical perspective of the socio-historical reality in which. The field research was supported by the collaboration of professionals of the occupational partner space of CRAS São Sebastião, who submitted the questionnaires with closed and open questions that talked about our professional practice, challenges, limits and perspectives for the profession front current conjuncture. Analyze the results from the perspective of urgent need for effective and materialization of Ethical-Political Project professional to a critical practice and consistent with the assumptions of the profession.